The microbiota-gut-brain axis and central nervous system diseases: from mechanisms of pathogenesis to therapeutic strategies - Xu, Jie; Lu, Yi (Frontiers in Microbiology, 2025)
The gut microbiota plays a crucial role in metabolic processes associated with host brain function. Emerging research is progressively uncovering the intricate and multifaceted relationship between the gut and the brain. The gut microbiota significantly influences immune responses, secondary metabolism, and symbiosis with the host, thereby facilitating the production of essential metabolites, neurotransmitters, and other neuroactive compounds that impact the development and treatment of central nervous system disorders. This article delineates the communication pathways and mechanisms linking the microbiota, gut, and brain, providing a comprehensive overview of current research on how the gut microbiota affects nervous system function. Furthermore, it examines factors that can alter the gut microbiota and influence metabolite profiles, as well as current intervention strategies aimed at enhancing gut-brain communication, mitigating adverse triggers that disrupt the gut microbiota, and minimizing neuro-pathological changes.